The effect of environmental approach on critical thinking ability in elementary school students' science content - Jupriyanto Jupriyanto; Sari Yustiana; Yunita Sari; Erista Indah Pratiwi (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2023)
This research is motivated by fifth-grade students' low critical thinking skills in science subjects. A learning approach is needed to overcome these problems. This study aims to determine the effect of the environmental approach on the science critical thinking skills of fifth-grade elementary school students. This research is an experimental quantitative research that uses the Quasi-Experimental Design used in this study, namely the Nonequivalent Control Group Design with data analysis paired sample t-test. The sample used in this study is fifth grade, as many as 35 elementary school students. It was concluded that from the results of the paired sample t-test hypothesis test, the results showed Sig. (2-tailed) 0.000. If Sig. (2-tailed) 0.000 < (0.05), then Ha is accepted, which means that there is an influence from the environmental approach on students' critical thinking skills.